2015
DOI: 10.1007/s00394-015-0999-6
|View full text |Cite
|
Sign up to set email alerts
|

Maternal zinc supplementation improves hepatitis B antibody responses in infants but decreases plasma zinc level

Abstract: Prenatal and postnatal zinc supplementation marginally improved T cell-dependent antibody responses in infants along with IL-7, a cytokine involved in human T cell development and maintaining homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 33 publications
0
45
0
Order By: Relevance
“…Post-hoc subgroup analyses were conducted for all outcomes, across all comparisons when ≥three studies per subgroup of interest were available. [49,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]). Seven studies were conducted in Latin America and the Caribbean [48,[113][114][115][116][117][118], and only one trial was conducted in Europe and Central Asia (Turkey; [52]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Post-hoc subgroup analyses were conducted for all outcomes, across all comparisons when ≥three studies per subgroup of interest were available. [49,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110][111][112]). Seven studies were conducted in Latin America and the Caribbean [48,[113][114][115][116][117][118], and only one trial was conducted in Europe and Central Asia (Turkey; [52]).…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies evaluated zinc supplementation compared to placebo in women during pregnancy [53,56,66,74,91,94,95,98,99,103,114,115,117]. Prawirohartono et al was not included in meta-analysis because it reported no poolable outcomes, but was narratively synthesized [53] (see Supplementary Materials, Table S3).…”
Section: Zinc Supplementation Versus Placebomentioning
confidence: 99%
See 2 more Smart Citations
“…It started in 1979 as a pilot project to eradicate or eliminate some vaccine preventable diseases [36]. HBV vaccine has been incorporated in EPI schedule since 2004 in Bangladesh and immunoprophylaxis of babies of HBsAg positive mother and post exposure prophylaxis are effective ways of prevention [37]. As many as 90% of infants born to Hepatitis B e Antigen (HBeAg) positive mothers become carriers themselves and, therefore, in long term are more likely to develop chronic liver disease [38].…”
Section: Overview On Epi and Hbv Vaccination In Bangladeshmentioning
confidence: 99%